PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN PROFITABILITAS TERHADAP AGRESIVITAS PAJAK DENGAN UKURAN PERUSAHAAN SEBAGAI PEMODERASI - Aminul Amin; Sarah Octaviani (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to examine the effect of corporate social responsibility and profitability on tax aggressiveness with firm size as a moderating variable. In this study, there are two independent variables, namely corporate social responsibility(X1) and profitability (X2). The dependent variable in this study is tax aggressiveness (Y). The moderating variable in this study is company size (X3). The population in this study are manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange in 2017-2019 as many as 144 companies. The method used is purposive sampling and obtained as many as 66 companies as samples. The hypothesis in this study was tested using SPSS. The results of this study indicate that 1) corporate social responsibility has no effect on tax aggressiveness 2) profitability has no effect on tax aggressiveness 3) company size has a negative effect on tax aggressiveness 4) company size is unable to moderate the influence betweencorporate social responsibility on tax aggressiveness 5) company size is able to moderate the effect of profitability on tax aggressiveness.